2014
DOI: 10.4238/2014.october.20.11
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between polyploidy and stressful environments? A case study of inselbergs in northeastern Brazil

Abstract: ABSTRACT. The aim of this study was to examine the hypothesis that plants with higher ploidy levels are selected by environments under more extremely stressful conditions than the same (or closely related) species from less rigorous terrestrial or epiphytic habitats. Therefore, we analyzed the chromosome numbers of 26 species belonging to 21 genera and 13 families of angiosperms that were collected on 4 inselbergs in Paraiba State, northeastern Brazil. In addition, 13 rupicolous species that grow in the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…Although the polyploidy proportions that we found are smaller, our results agree with the conclusion of that polyploidy is less frequent in tropical regions. Other studies have come to similar conclusions (Martin and Husband 2009;Glennon et al 2014;Pitrez et al 2014;Visser and Molofsky 2015).…”
Section: Table 1)supporting
confidence: 66%
See 3 more Smart Citations
“…Although the polyploidy proportions that we found are smaller, our results agree with the conclusion of that polyploidy is less frequent in tropical regions. Other studies have come to similar conclusions (Martin and Husband 2009;Glennon et al 2014;Pitrez et al 2014;Visser and Molofsky 2015).…”
Section: Table 1)supporting
confidence: 66%
“…Several studies have compared the frequency of polyploids in natural angiosperm communities across environmental stress gradients in Europe (Löve 1953), North America Martin and Husband 2009), Artic (Brochmann et al 2004), inselbergs in northeastern Brazil (Pitrez et al 2014), and the world flora . and Brochmann et al (2004) have observed that polyploids were more frequent in harsh environments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apocynaceae is a globally distributed family consisting of about 400 genera and 5000 species (Endress & al., 2007). In Brazil, about 750 species occur in different kinds of habitat, including inselbergs (Rapini, 2012;Pitrez & al., 2014a). The family is characterized by a remarkable diversity in chromosome numbers, ranging from 2n = 10 in Rhabdadenia madida (Vell.)…”
Section: Subfamily Mapanioideae Tribe Chrysitricheaementioning
confidence: 99%